Information technologies for progress of boxing in Russian Federation - Polozov, A. A.; Tszu, K. B.; Shurmanov, E. G. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to analyze benefits of modern automatic rating systems for boxers and referees.